Antidepressant use during pregnancy and the risk for gestational diabetes: a systematic review and meta-analysis - Wang, Xiao-yan; Ying, Xian-hua; Jiang, Hai-yin (The journal of maternal-fetal & neonatal medicine, 2023)
Antidepressant medications are used by increasing numbers of pregnant women. The evidence on the relationship between antidepressant use during pregnancy and the risk for gestational diabetes mellitus (GDM) is inconsistent. We perform a systematic review and meta-analysis to assess the GDM risk associated with antidepressant exposure during pregnancy. We systematically searched the PubMed and EMBASE databases until December 2021. We sought observational studies assessing the association between gestational antidepressant use and GDM. Five observational studies were included in the analysis. Mothers exposed to antidepressants during pregnancy were at a significantly increased risk for GDM (relative risk [RR] 1.20, 95% confidence interval [CI] 1.11-1.30; p < .001). However, after considering confounding by indication, we observed no significant effect of antidepressant use during pregnancy on the risk of GDM (RR 1.13, 95% CI 1-1.28; p = .054; I 2 = 0%). Independent of clinical indication, subgroup analysis based on individual antidepressants suggested that the risk was increased by venlafaxine or amitriptyline use, but not by selective serotonin reuptake inhibitors. The significant association between antidepressant exposure during pregnancy and GDM may be overestimated due to confounding by indication. However, the evidence remains insufficient, particularly for specific drug classes.